The importance of diet and metabolism: from nutrition to allergy and immunology - Stefania Colantuono; Ilaria Baglivo; Cristiano Caruso (Nutrimentum et Curae)
Food represents not only the source of nutrients for our body, but interacts with the gastrointestinal epithelium, gut microbiome and gut immune system. The diet-immune systems interactions are complex and reciprocal. Various recent studies attempted to explore this complexity in health and in different disease settings in order to untangle the mechanisms and their effects.